Effectiveness of Discovery learning Models Assisted by Puzzle Mind maps on the Activities and Learning Outcomes of the Structure and Function of Animal Tissue Materials - Milatina Murni Lestari; Nugrahaningsih WH; Nur Rahayu Utami (EduResearch Mitra Inovasi, 2019)
A The research aims to determine the effectiveness of discovery learning models assisted by puzzle mind maps on the activities and learning outcomes of the Structure and Function of Animal Tissue Materials. This research was conducted at SMAN 13 Semarang in the Odd Semester Academic Year 2018/2019. This research is a Quasi Experiment study with Nonequivalent Control Group Design. The population in this research were all students of Class XI MIPA of SMAN 13 Semarang. The sample used was Class XI MIPA 1 and XI MIPA 2 which was taken by purposive sampling technique. The results showed that the learning outcomes showed that there were no significant differences between the learning outcomes of the control class and the experimental class (sig. ˃ 0.05). Data on student activity obtained by observation and filling in questionnaire sheets showed that 100% of the experimental class students entered very active and active category, while in the control class showed that 89.3% of students entered were very active and active category. This shows that the experimental class is able to surpass the indicator ≥ 90% in the student activity. The conclusion is the application of discovery learning models assisted by puzzle mind map of the Structure and Function of Animal Tissue Materials effectively applied to increase student activity but not to improve learning outcomes.